Environmental ethics of Kuta traditional village community in preserving the environment and its future prospects - Nisa, Ainun; Surtikanti, Hertien Koosbandiah (Institute for Advanced Science Social, and Sustainable Future, 2024)
Environmental conservation is a major global issue, with Indonesia ranking low in the Environmental Performance Index 2022. This study focuses on Kampung Adat Kuta, a community in Ciamis, West Java, which upholds local wisdom in maintaining the balance of nature as one of the sustainable environmental ethics and its future prospects. The methods used in this research are literature study and bibliometric analysis. The results show that customary rules, such as respecting sacred forests, building houses according to the rules of the ancestors, and the prohibition of making wells, reflect local wisdom that supports environmental conservation. The people of Kampung Adat Kuta also uphold the concept of